Pemanfaatan Museum Keprajuritan Indonesia sebagai Sumber Belajar Sejarah - Evita Dwi Oktaviani (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2020)
This study aims to provide an overview of how the use of the Museum of the Indonesian Army as a source of history learning in history lesson. The research method used was qualitative with a descriptive approach, and the technique of collecting or collecting data through observation, interviews and documentation studies. The results of the research concluded that: (1) The Museum of the Indonesian Army can be used as a source of history learning because the museum has relevance to Indonesian history lesson in class X basic competencies 3.6 and 3.8, while class XI basic competency 3.2. (2) The obstacles faced in using the museum as a source of historical learning, namely the lack of human resources that affect the managerial aspects of service and management of the museum is less than the maximum. The lack of museum operational funds. The difficulty of the difficult permission from the school bureaucracy. There is no museum visit program. Lack of attention and socialization from the museum manager. (3) Educational programs carried out by the Museum of the Indonesian Army can help improve the existence of museums and optimize the function of museums as a source of historical learning. Penelitian ini bertujuan untuk memberikan gambaran bagaimana pemanfaatan museum keprajuritan Indonesia sebagai sumber belajar sejarah pada mata pelajaran sejarah. Metode penelitian yang digunakan adalah kualitatif dengan pendekatan deskriptif, dan teknik pengambilan atau mengumpulkan data melalui observasi, wawancara dan studi dokumentasi. Hasil penelitian menyimpulkan bahwa: (1) Museum Keprajuritan Indonesia dapat dimanfaatkan sebagai sumber belajar sejarah karena museum tersebut memiliki relevansi dengan mata pelajaran sejarah Indonesia kelas X kompetensi dasar 3.6 dan 3.8, sedangkan kelas XI kompetensi dasar 3.2. (2) kendala yang dihadapi dalam memanfaatkan museum sebagai sumber belajar sejarah, yaitu Kurangnya SDM yang mempengaruhi aspek manajerial pelayanan dan pengelolaan museum menjadi kurang maksimal. Minimnya dana operasional museum. Sulitnya perijinan yang sulit dari birokrasi sekolah. Tidak adanya program kunjungan ke museum. Kurangnya perhatian dan sosialiasasi dari pengelola museum. (3) Program edukasi yang dilaksanakan oleh Museum Keprajuritan Indonesia dapat membantu meningkatkan eksistensi museum dan mengoptimalkan fungsi museum sebagai sumber belajar sejarah.